Analysis of Total Flavonoid Content in the Extract of Bajakah Kalalawit Root (Uncaria gambir Roxb) Infunded Results - Nurul Reza Alfani; Rizki Febrianti; Wilda Amananti (Universitas Negeri Medan, 2023)
Bajakah kalalawit is one of the plants that has been empirically used in traditional medicine. The roots of Bajakah kalalawit (Uncaria gambir Roxb) have phenol and antibacterial content and have a high enough content of flavonoid compounds so that they have pharmacological activity as an anticancer. This article examines the content of flavonoid compounds contained in the extract of Bajakah Kalalawi root and also examines the total levels of flavonoids contained in the roots of Bajakah Kalalawi. Bajakah kalalawit root extract was obtained by the infundation extraction method using a water solvent (1:10). Examination of the characteristics of the sample is carried out by macroscopic and microscopic identification. The qualitative test of flavonoids was carried out by color reaction tests in two treatments. Determination of flavonoid levels in the root extract of bajakah kalalawi was carried out by the UV-Vis spectrophotometry method. From the results of the study showed that the levels of flavonoids in the root extract of Bajakah Kalalawi in sample A were 33.2% and in sample B by 44.8%. The results showed that the roots of Bajakah Kalalawi were shown to contain flavonoid compounds.